MODIFIKASI POLISTIREN MELALUI KOPOLIMERISASI BERSAMA POLI-E-KAPROLAKTON DAN KARAKTERISASINYA - Fitri A, Ristny
Poly-?-caprolactone (PCL) is one of environmental friendly polyester. Characteristics of this compounds are low melting point, Tm around 60 °C, and very crystalline. Its high crystallinity caused this polymer quite brittle. The application of this material has been used commercially as fiber, coating, and implantable biomaterial. However, PCL cannot be applied as plastic due to low mechanical and thermal properties of PCL. In the other hand, polystyrene (PS) has better melting point, Tm around 190-270 °C and good mechanical properties at room temperature. PS can be processed easily and very economically cheap. Its application as packing material in very long-time caused plastics waste problem. Biodegradable polymers are promising solution for solving these problems. To solve plastic waste problem and to improve PCL capability, PCL can be copolymerized with PS to become biodegradable polymers with good mechanical properties. In this research, copolymerization between PCL and styrene has been carried out for 20 hours by using dibenzyl- peroxide (DBP) as an initiator. The variation of composition between PCL and St were CL/St= 1/9, 2/8, 3/7, 5/5, and 7/3. PCL was synthesized by ring opening polymerization mechanism for 8 hours. FTIR analyses showed that there were shifting characteristic peaks for PCL and PS in copolymer. Crystallinity of copolymers was increased by increasing composition of PCL in copolymer. Based on viscosity analyses, copolymers of PCL and St have higher intrinsic viscosity than pure PCL. TG/DTA thermograms indicated melting point of PCL part about 60 °C, and two decomposition regions for PCL and PS. GPC analysis shows that copolymers have different molecular weight distribution and higher average molecular weight ( w M ) than pure PCL.